The Implementation of Authentic Assessment in Speaking Tests for Secondary School Students - Karisma Putri Lestari, Leady; Rahmawati, Fithriyah; Amelia, Indah; Utami, Nita Aprilia; Handayani, Rini (Penerbit STKIP PGRI Bangkalan, 2025)
The use of authentic assessment in speaking tests has gained greater significance to close the gap between theory and practice in the classroom. Although its value in measuring actual language skills in everyday life is known, its effective implementation by teachers remains a problem and inconsistencies in measuring students' speaking skills are the result. This study aims to explore the implementation of authentic assessment in speaking tests in SMA Negeri 5 Pamekasan, namely the implementation processes employed by teachers and the impact towards the students' actual speaking abilities. Conducting a qualitative descriptive study, data were collected using interviews, observation, and documents to represent the naturalistic nature of the classroom and the teachers' assessment strategies. The study reveals that SMA Negeri 5 Pamekasan teachers have informal and formative tests that involve reading aloud, pronunciation, intonation, and confidence measures in classroom interactions. Question-answer and reading aloud are some of the strategies used to overcome the students' shyness to speak and judge more realistically their communications. The study concludes that authentic assessment, when properly understood and implemented, exactly measures students' speaking skill under actual circumstances and helps teachers know how to direct further improvement. This study provides implications and pedagogical suggestions for teachers to enhance authentic assessment practice in English speaking courses.